Perancangan Ontologi Semantik: Representasi Digital Kain Songket Bali - Gunawan, I Made Suma; Astuti, Luh Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 4 (2023): JNATIA Vol. 1, No. 4, Agustus 2023, 2023)
Advances  in information technology are currently driving an increase  in  the number of internet users. In the business world, technology plays an important role and can be considered as a basic necessity for today's entrepreneurs. Likewise, in the textile industry, especially Balinese songket craftsmen or entrepreneurs, it is very important to utilize digital platforms to assess the results of Balinese songket fabrics and manage various aspects properly such as quality, color and pattern, innovation,  and  price.  Thus,  this  knowledge  can  be  shared  with  the  public,  passed  down  from generation  to  generation,  and  promoted  to  both  local  and  foreign  tourists,  thereby  increasing industry recognition and contributing to the country's foreign exchange earnings. To achieve this, the  use  of  ontologies  as  an  information  representation  technique  is  highly  favored.  Ontologies can greatly facilitate the development of semantic applications, especially when dealing with the semantic web. The methodology used for the development of the ontology model in this study is a process that allows the reuse of existing ontologies in subsequent system development. The development of the ontology model in this study uses a software application called Protégé, which has  shown  promising  results  during  the  ontology  evaluation  stage  in  providing  satisfactory answers to user questions.